(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Location-based service is a rapidly growing mobile service group in the mobile technology world. Upon their permissions, location information of consumers can be used to provide them with marketing-related messages and information. However, certain factors have to be considered in order to increase consumers willingness to participate in location-based marketing activities. In this article, those factors have been investigated in an merging country, namely Turkey. After a thorough literature review on mobile marketing, location-based mobile marketing and relevant areas topics discovered have been checked with mobile marketing professionals in Turkey through in-depth interviews. A model has been proposed covering factors that affect mobile marketing and a scale has been developed. Statistical analyses were performed using the data collected from 364 surveys. As a result, personal innovativeness, personalization, permission, perceived ease of use, mobile marketing experience, perceived usefulness and perceived trust have proven to have an effect on the intention of consumers to participate in location-based mobile marketing.